Dynamical, biological, and anthropic consequences of equal lunar and solar angular radii - Balbus, S (Royal Society of London, 2014)
The nearly equal lunar and solar angular sizes as subtended at the Earth is generally regarded as a coincidence. This is, however, an incidental consequence of the tidal forces from these bodies being comparable. Comparable magnitudes implies strong temporal modulation, as the forcing frequencies are nearly but not precisely equal. We suggest that on the basis of paleogeographic reconstructions, in the Devonian period, when the first tetrapods appeared on land, a large tidal range would accompany these modulated tides. This would have been conducive to the formation of a network of isolated tidal pools, lending support to A.S. Romer's classic idea that the evaporation of shallow pools was an evolutionary impetus for the development of chiridian limbs in aquatic tetrapodomorphs. Romer saw this as the reason for the existence of limbs, but strong selection pressure for terrestrial navigation would have been present even if the limbs were aquatic in origin. Since even a modest difference in the Moon's angular size relative to the Sun's would lead to a qualitatively different tidal modulation, the fact that we live on a planet with a Sun and Moon of close apparent size is not entirely coincidental: it may have an anthropic basis.